محمد ناصر مفكِّرًا ومصلحًا: فكره الديني والسياسي والاجتماعي = Mohammad Natsir as thinker and reformer: his religious, political and social thought - Nasser, Youcef; Solihin, Sohirin Mohammad (University of Tlemcen- Algeria, 2019)
يعالج هذا البحث التطورات الفكرية والدينية في مسيرة المفكِّر والمصلح الإندونيسي محمد ناصر؛ حيث يتطرَّق إلى فكره الديني والسياسي الذي وقف على مبدأ ظل ثابتًا عليه حتى مماته، وهو أن الإسلام دين ودولة، وذلك من غير أن ينفي طبيعة الحكم الديمقراطي إنْ هو جلب التنمية والعدالة للناس. كما يبرز هذا البحث وقوف محمد ناصر على أهمية القيم الدولية والأفكار القومية في نجاح العملية الديمقراطية إذا كانت تستجيب للمطالب البيئية للأغلبية المسلمة في إندونيسيا، وتعزِّز من فرص التسامح الديني بين الأعراق والديانات. ومن زاوية أخرى يتناول هذا البحث، أيضًا، الفكر الديني والاجتماعي لدى محمد ناصر الذي له تصوراته الإسلامية المبدعة لمفهوم العبادة وأصول القيادة؛ ما يجعل الاستفادة من أفكار محمد ناصر الدينية والسياسية والاجتماعية ضرورة من أي وقت مضى للخروج من الأزمات التي تطال الأحزاب الإسلامية وتنسف مشروعاتها الإنمائية التي باتت تصطدم بفهم المسلمين الخاطئ للديمقراطية في أبعادها الإنسانية والإنمائية. ********************************************************** The paper attempts to highlight developmental religious thought of Mohammad Natsir as a thinker and reformer of Indonesia. It mainly deals with his thought related to religion and political orientation under the theme ‘Islam as religion and state’ which he subscribed to it throughout his life. Mohammad Natsir did not negate the use of democratic system whenever it brings about the progress and justice. Moreover, the paper also discusses the stand of Mohammad Natsir in endorsing what so-called universal values and the concept of nationalism to galvanize the implementation of democracy to serve Muslim majority in Indonesia. In addition, it also sheds more light on his vision with regard to the concept of tolerance across ethnical background and religious adherents. The other aspect it focuses on revealing distinctive thought of Mohammad Natsir related to religious and sociological thought, spirituality and leadership. How far his vision on religious, political and sociological thought are relevant to be applied today in offering solution from political crisis experienced by Muslim parties which is simply due to the shortcoming of program which, at the end, brings about negative impression to Muslims on democracy, humanity and development.